Optimizing Process Parameter of Friction Stir Welding on Aluminium Using Response Surface Methodology - Mohd Amin, Azriszul; Mohamad Idris, Aida Arinah (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Friction stir welding (FSW) has been widely experimented on manufacturing industry due to its broad engineering applications. FSW technique results in the material having low distortion and high joint strength as compared with other joining techniques. The purpose of this study is to analyse the effect of various process parameters such as rotational speed, welding speed and tool geometries on the joining process of aluminium alloy then determine the optimum process parameter. Every year, friction stir welding techniques advances and revolutionises the process. Owing to its excellent weld strength compared to other welding techniques, it is utilised to weld aluminium alloys in a variety of industries. However, FSW on aluminium alloys frequently results in substantial complications in the setting of welding parameters due to the constraints of joining the material. Hence, the need to determine the optimum process parameters is critical. The optimization of process parameter is done after completing the welding procedure by using design of experiment (DOE) concept which is response surface methodology in Minitab software. In this study, central composite design technique and mathematical model was developed by response surface methodology with three process parameters and 20 runs, was used to develop the relationship between the FSW parameters  and the responses, tensile strength were established. The results show that the triangular welding tool pin, 1200 rpm rotational speed and 60 mm/min welding have the highest tensile strength which is 169 MPa. The optimum parameter of the FSW process evaluated by the response optimizer are 1200 rpm rotational speed, 30 mm/min welding speed and triangular tool pin geometry.